Driver distraction and inattention in the realm of automated driving. Issue 6 (5th January 2018) - Cunningham, Mitchell L.; Regan, Michael A.
Abstract : Despite the increasing number of automated systems that have been introduced in vehicles over the past decade, highly automated vehicles are not yet capable of driving reliably and safely in all traffic scenarios and conditions. Until they are, humans will need to remain in the loop – to take back vehicle control when the driving capabilities of the automated system(s) are limited or systems fail. This automation‐to‐manual transition may be problematic if the driver is inattentive or distracted by competing activities. If so, this may compromise the driver's ability to take back control in a safe and timely manner. The aims of this study are to: (a) review what is known about driver inattention and distraction during periods of highly automated driving, (b) to outline countermeasures that have or may have potential to prevent and mitigate the effects of inattention and distraction during automated driving and (c) to highlight future research directions that may further inform the understanding and management of distraction and inattention as vehicles become increasingly automated. The paper concludes by contemplating whether a fully self‐driving vehicle may itself be distracted or inattentive to activities critical for safe driving.